Velocity field and pressure analysis of equatorial flows beneath solitary water waves. (February 2023) - Li, Qixiang; Fečkan, Michal; Wang, JinRong
Abstract: In this paper, we investigate steady equatorial flows beneath solitary water waves subject to the Coriolis effect, which propagate over a flat bed. In particular, we focus on irrotational flows and present some properties of velocity field, behavior of the pressure and the extrema of the dynamic pressure. In addition, we provide some estimates for the elevation of wave from pressure measurements at an arbitrary intermediate depth. The analysis is based on the maximum principles.